MRS-bile agar: Its Suitability for the Enumeration of Mixed Probiotic Cultures in Cultured Dairy products - Mortazavian, Amir Mohammad (2006)
This paper contains a study on the suitability of MRS-bile agar medium for enumeration of mixed probiotic cultures in cultured dairy products, beside an analysis of the morphological characteristics of probiotic colonies using SDM (stereo digital microscopy) method. Three probiotic cultures (Lactobacillus acidophilus, Lactobacillus casei and bifidobacteria) were enumerated in various mixed culture compositions, i.e. AY (L. acidophilus and yogurt bacteria), CY (L. casei and yogurt bacteria), BY (bifidobacteria and yogurt bacteria), ABY (L. acidophilus, bifidobacteria and yogurt bacteria), ACY (L. acidophilus, L. casei and yogurt bacteria) and BCY (bifidobacteria, L. casei and yogurt bacteria). MRS-bile agar showed a good suitability for differential enumeration of probiotics in ACY culture composition under both aerobic and anaerobic conditions, differential and selective enumeration of probiotics in BCY culture composition (anaerobiosis and aerobiosis, respectively) and selective enumeration in ABY culture composition only for L. acidophilus under aerobiosis. Furthermore, by the subtractive enumeration method (SEM) proposed in this article, based on the subtraction of the colonies growth under aerobic condition (only L. acidophilus) from the colonies growth under anaerobic condition (both L. acidophilus and bifidobacteria), the number of bifidobacteria in ABY culture composition could also be well determined.